Respuesta :
Answer:
4hx - 8x - 3h - 4
k = ------------------------
5
8x + 5k + 4
h = ------------------------
4x - 3
Step-by-step explanation:
4 (hx - 1) - 3 (x + h) = 5 (x + k)
4hx - 4 - 3 (x + h) = 5 (x + k)
4hx - 4 - 3x - 3h = 5 (x + k)
4hx - 4 - 3x - 3h = 5x + 5k add 3h both sides
4hx - 4 - 3x - 3h + 3h = 5x + 5k + 3h simplify
4hx - 4 - 3x = 5x + 5k + 3h add 4 both sides
4hx - 4 - 3x + 4 = 5x + 5k + 3h + 4 simplify
4hx - 3x = 5x + 5k + 3h + 4 subtract 5x from both sides
4hx - 3x - 5x = 5x + 5k + 3h + 4 - 5x simplify
4hx - 8x = 5k + 3h + 4
4hx - 8x - 3h - 4 = 5k
4hx - 8x - 3h - 4
k = ------------------------
5
solving for h;
4hx - 3h = 8x + 5k + 4
h(4x - 3) = 8x + 5k + 4
8x + 5k + 4
h = ------------------------
4x - 3
The value of h and k are h = (8x + 5k + 4) / (4x - 3) and k = (4hx - 8x - 3h - 4) / 5 respectively
Given:
4 (hx - 1) -3 (x +h) ≡ 5 (x + k)
open parenthesis
4hx - 4 - 3x - 3h = 5x + 5k
4hx - 4 - 3x - 3h - 5x - 5k = 0
4hx - 8x - 3h - 5k - 4 = 0
For k
4hx - 8x - 3h - 4 = 5k
[tex]k = (4hx - 8x - 3h - 4) / 5[/tex]
For h
4hx - 8x - 3h - 5k - 4 = 0
4hx - 3h = 8x + 5k + 4
h(4x - 3) = 8x + 5k + 4
[tex]h = (8x + 5k + 4) / (4x - 3)[/tex]
Therefore, the value of h and k are h = (8x + 5k + 4) / (4x - 3) and k = (4hx - 8x - 3h - 4) / 5 respectively
Read more:
https://brainly.com/question/21406377